Strategi Mahasiswa Di Daerah Terisolir Dalam Mengatasi Kendala Jaringan (Analisis Sosiologi Proses Pembelajaran Daring Di Kecamatan Mapat Tunggul Kabupaten Pasaman - Novrensistri Novrensistri; Marleni Marleni; Yanti Sri Wahyuni (Horizon, 2021)
This research is motivated by the existence of a virus called Covid-19. This virus has entered various countries so that all activities are limited, including education which makes the learning process online (in the network). The same is true for students who live in Mapat Tunggul District, West Pasaman Regency, which is an isolated area, so that students there experience network problems when carrying out the online learning process. The formulation of the research problem is how the strategy of students in isolated areas to get internet network access for online learning in Mapat Tunggul District, Pasaman Regency. The theory used in this study is the structural-functional theory proposed by Talcott Parsons. The research approach used is a qualitative approach with a descriptive type of research. The types of data used in this study are primary data and secondary data. The informants involved experienced this network problem as many as 13 people. Data collection methods were used in two ways, namely observation, in-depth interviews and document studies. To achieve the validity of research data using triangulation techniques. Meanwhile, the unit of data analysis used was a group with data analysis by Miles and Huberman, namely data reduction, data presentation, data presentation and conclusion drawing. From the results of the study it can be concluded that there are several strategies undertaken by students in overcoming network constraints such as students building social relations with fellow students studying online at hill 7, with the hill community 7, forming social groups with fellow friends who attend online lectures, and build social relations with neighbors.